Dexamethasone in Glioblastoma Multiforme Therapy: Mechanisms and Controversies - Cenciarini, Marta; Valentino, Mario; Belia, Silvia; Sforna, Luigi; Rosa, Paolo; Ronchetti, Simona; D’Adamo, Maria Cristina; Pessia, Mauro (Frontiers in Molecular Neuroscience, 2019)
Glioblastoma Multiforme (GBM) is the most commonly occurring brain tumour. The world-wide estimation of annual new cases of GBM and deaths are remarkable, making GBM a crucial public health issue. Despite the combination of radical surgery, radio and chemotherapy prognosis is extremely poor (median survival is approximately 1 year). Thus, current therapeutic interventions are highly unsatisfactory. For many years, GBM-induced brain oedema and inflammation have been widely treated with dexamethasone (DEX), a synthetic glucocorticoid. A number of studies have reported that DEX also inhibit GBM cell proliferation and migration. Nevertheless, controversial results have been recently provided by different laboratories, challenging widely accepted dogma concerning DEX therapy for GBM. Here, we have reviewed the main clinical features and pathogenic mechanisms underlying GBM, analyzed critically current notions and concerns related to DEX effects on cerebral oedema, cancer cells proliferation and migration and patient’s clinical outcome.